Pelatihan Deteksi Dini Penyakit Kusta Pada Anak Kepada Guru Sekolah Dasar Di Wilayah Kerja Puskesmas Sanggeng Manokwari - Yayuk Nuryanti; Waode Suriani (Universitas Lancang Kuning, 2022)
In Indonesia, the proportion of people with leprosy in children is still above 5%, which indicates the high transmission rate in the local area. Data in 2020, cases of leprosy in children in the Sanggeng Helath Center area were 52%. School Health Effort is a vehicle for teaching and learning in improving a healthy lifestyle, wich is coordinated by a teacher. One of the activities is a health check. The Sanggeng Health Center has never conducted training on early detection of leprosy for elementary school teachers. The method of activity is by conducting training on early detection of leprosy in children, with 22 participants. The implementation of activities includes pretest, giving material, demonstration, practise and postest. The evaluation results obtained a pretest with an average value of 62, while the posttest with average value of 88. Subjective data obtained at the beginning of the activity, participants said they did not know how to detect leprosy early, objective data was obtained that participants did not know how to do early detection of leprosy in children. Evalation of the result of the activity obtained subjective data from participants who said they were able to carry out early detection of leprosy in childdren, and objective data obtained that participants were able to perform early detection of leprosy in children. Conclusion traing can improve knowledge and skills. As to folow-up this activity, the teacher can conduct an aerly detectipn of leprosy. If suspicion is found, immediately coordinate wiyh parents and refer to Puskesmas.